Feasibility of chitosan crosslinked with genipin as biocoating for cellulose-based materials. (15th August 2020) - Oliveira, Gonçalo; Gonçalves, Idalina; Nunes, Cláudia; Ferreira, Paula; Coimbra, Manuel A.; Martin, Céline; Bras, Julien
Graphical abstract: Abstract: Crosslinking with genipin increases the acidic stability of chitosan-based materials, opening an opportunity to explore new applications. In this work, the viability of using chitosan-genipin solutions on cellulose-based materials coating was studied. Non-calendered paper and cardboard were used as raw materials. Different number of chitosan-genipin coating layers (1, 3, 6, 20, and 30) were applied and their influence on the materials mechanical, physicochemical, and barrier properties was studied. The small thickness and basis weight of non-calendered paper resulted in an inefficient adhesion of chitosan-genipin coating to the cellulose fibers. However, in cardboard, chitosan-genipin created a dense layer onto the cellulosic-fibers surface without impairing their mechanical properties. It conferred a greenish color, whose intensity increased with the layers number. The chitosan-genipin coating decreased the cardboard air and water vapor permeability up to 71 % and 52 %, respectively, and acted as a physical barrier for cardboard compounds leaching, being suitable for covering cellulose-based materials.